Theme Issue Honoring Prof. Dr. Ludger Wessjohann's 60th Birthday: Natural Products in Modern Drug Discovery (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nature continuously produces biologically useful molecules and provides humankind with life-saving drugs or therapies. Natural products (NPs) offer a vast, unique and fascinating chemical diversity and these molecules have evolved for optimal interactions with biological macromolecules. Moreover, natural products feature pharmacologically active pharmacophores which are pharmaceutically validated starting points for the development of new lead compounds. Over half of all approved (from 1981 to 2014) small-molecule drugs derived from NPs, including unaltered NPs, NPs synthetic derivatives and synthetic natural mimics, originated from a NPs pharmacophore or template. According to the FDA, NPs and their derivatives represent over one-third of all FDA-approved new drugs, in particular for anticancer/antibiotic lead compounds, which are remarkably enriched with NPs.